Regulatory Mechanisms of Soft Palate Development and Malformations. (August 2019) - Li, J.; Rodriguez, G.; Han, X.; Janečková, E.; Kahng, S.; Song, B.; Chai, Y.
Orofacial clefting is the most common congenital craniofacial malformation, appearing in approximately 1 in 700 live births. Orofacial clefting includes several distinct anatomic malformations affecting the upper lip and hard and soft palate. The etiology of orofacial clefting is multifactorial, including genetic or environmental factors or their combination. A large body of work has focused on the molecular etiology of cleft lip and clefts of the hard palate, but study of the underlying etiology of soft palate clefts is an emerging field. Recent advances in the understanding of soft palate development suggest that it may be regulated by distinct pathways from those implicated in hard palate development. Soft palate clefting leads to muscle misorientation and oropharyngeal deficiency and adversely affects speech, swallowing, breathing, and hearing. Hence, there is an important need to investigate the regulatory mechanisms of soft palate development. Significantly, the anatomy, function, and development of soft palatal muscles are similar in humans and mice, rendering the mouse an excellent model for investigating molecular and cellular mechanisms of soft palate clefts. Cranial neural crest–derived cells provide important regulatory cues to guide myogenic progenitors to differentiate into muscles in the soft palate. Signals from the palatal epithelium also play key roles via tissue-tissue interactions mediated by Tgf-β, Wnt, Fgf, and Hh signaling molecules. Additionally, mutations in transcription factors, such as Dlx5, Tbx1, and Tbx22, have been associated with soft palate clefting in humans and mice, suggesting that they play important regulatory roles during soft palate development. Finally, we highlight the importance of distinguishing specific types of soft palate defects in patients and developing relevant animal models for each of these types to improve our understanding of the regulatory mechanism of soft palate development. This knowledge will provide a foundation for improving treatment for patients in the future.